Automated Car Safety Enhancement System - Ooi Hooi Shih (Universiti Malaysia Perlis, 2008)
Automated Car Safety Enhancement Systems (ACSES) is a system that designed to prevent accidents or to minimize the force and damage of collision in case of accidents. The goal of this system is to help avoiding vehicle crashes, or at least mitigating of host vehicle on rear-end collision which rear-end collisions are one of the most common. Automated Car Safety Enhancement System scans and monitors the direct environment of the vehicle for potential dangers. When detected, the potential danger of crashing is determined and, if so, a system action is undertaken by giving vision or audio alert to the drivers. The main objective of this project is to develop a prototype model for the rapid prototyping and testing the system. In this project, it was divided into two parts which involve hardware and software environment for both parts. The first part is called as Intelligent Night-time Alert System (iNAS), while the second part is called as Intelligent Third Brake System (iTBS). The details design and implementation for both systems are presented in this report. Finally, the results are discussed and summarized. Suggestions and feature enhancements of the system for future improvements are also proposed.